Pulmonary Function Tests in Emergency Department Pediatric Patients with Acute Wheezing/Asthma Exacerbation - Giordano, Kathryn; Rodriguez, Elena; Green, Nicole; Armani, Milena; Richards, Joan; Shaffer, Thomas H.; Attia, Magdy W. (Pulmonary Medicine, 2012)
Background. Pulmonary function tests (PFT) have been developed to analyze tidal breathing in patients who are minimally cooperative due to age and respiratory status. This study used tidal breathing tests in the ED to measure asthma severity. Design/Method. A prospective pilot study in pediatric patients (3 to 18 yrs) with asthma/wheezing was conducted in an ED setting using respiratory inductance plethysmography and pneumotachography. The main outcome measures were testing feasibility, compliance, and predictive value for admission versus discharge. Results. Forty patients were studied, of which, 14 (35%) were admitted. Fifty-five percent of the patients were classified as a mild-intermittent asthmatic, 30% were mild-persistent asthmatics, 12.5% were moderate-persistent asthmatics, and 2.5% were severe-persistent. Heart rate was higher in admitted patients as was labored breathing index, phase angle, and asthma score. Conclusions. Tidal breathing tests provide feasible, objective assessment of patient status in the enrolled age group and may assist in the evaluation of acute asthma exacerbation in the ED. Our results demonstrate that PFT measurements, in addition to asthma scores, may be useful in indicating the severity of wheezing/asthma and the need for admission.